The Effect of Product Quality and Brand Awareness on Consumers’ Purchase Intention: The Mediating Role of Social Media Marketing - Galon Pernando Sigalingging; Hery Winoto Tj (Goodwood Publishing, 2026)
Purpose: This study examines the effects of product quality and brand awareness on skincare purchase intention, with social media marketing as a proposed mediating mechanism, among Generation Z consumers in Jakarta. Methodology: Data were collected from 100 Generation Z consumers in Jakarta with prior skincare usage experience, using a cross-sectional survey. Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4.0 was used to analyze the data, assessing direct and indirect relationships among the constructs. The measurement model showed satisfactory reliability and validity. Results: Product quality and brand awareness significantly influence social media marketing, which, in turn, affects purchase intention. However, social media marketing did not mediate the relationship between product quality or brand awareness and purchase intention. All three constructs—product quality, brand awareness, and social media marketing—exert significant positive effects on purchase intention. Conclusions: Product quality and brand awareness remain the dominant drivers of purchase intention for Generation Z consumers, operating independently of social media marketing. Limitations: The study's focus on Generation Z consumers in Jakarta limits the generalizability of findings to other regions or age groups. Additionally, social media marketing did not mediate the relationship between product quality or brand awareness and purchase intention, suggesting the need for further research on other mediators. Contribution: This study adds to the literature on consumer behavior and digital marketing by highlighting the limited role of social media marketing as a mediator in the skincare purchase context in emerging markets.